Solid state synthesis, x-ray diffraction and scanning electron microscopy of rare-earth silicate apatite - Lim, Soo Min (2014)
Apatite structures have great potential in the area of nuclear waste stabilization due to the steady columns of polyhedron within its crystal structure. Since during the process of nuclear waste disposal, apatite structures are required to remain stable at elevated temperatures, making britholite apatite a promising matrix for this project with the chemical formula of RE8Sr2(SiO4)6O2.This thesis illustrates the study of crystal structures regarding rare earth element (REE) britholite apatite via solid state using different characterization techniques.